The impact of color palettes on the prices of paintings - Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
We emphasize that color composition is an important characteristic of a painting. It impacts the auction price of a painting but it has never been considered in previous studies on art markets. By using Picasso's paintings and paintings of Color Field Abstract Expressionists sold in Chrisite's and Sotheby's auctions in New York between 1998 and 2016, we demonstrate the method to analyze color compositions: how to extract color palettes from a painting image and how to measure color characteristics. We propose two measures: 1) the surface occupied by specific colors, 2) color diversity of a painting composition. Controlling for all conventional painting and sale characteristics, our empirical results find significant evidence of contrastive paintings, i.e. paintings with high diversity of colors, carrying a premium than equivalent artworks which are performed in monochromatic style. In the case of Picasso's paintings, our econometric analysis shows that some colors are associated with high prices.
Keywords: Z11; C810; 330; art markets; hedonic pricing; Picasso; Rothko; visual data; color; color quantizing